Legal Review of the Execution of Mortgage Rights on Land : (Study of Constitutional Court Decision Number 10/PUU-XIX/2021) - Triwanto Triwanto; Puspaningrum Puspaningrum; Dita Permata Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
The execution of mortgage rights on land is a crucial element in the property security legal system in Indonesia, which allows creditors to obtain debt repayment if the debtor defaults. However, the implementation of parate executie as a non-litigious mechanism based on Law Number 4 of 1996 concerning Mortgage Rights has sparked constitutional debates, particularly regarding the debtor's right to fair legal protection. This study analyzes the legal considerations of the Constitutional Court in Decision No. 10/PUU-XIX/2021, which rejected the constitutional review of the mortgage execution norms, and evaluates the legal execution procedures post-decision. Using the normative legal research method, this article examines the approach of contractual freedom, the principle of justice, and the protection of property rights in the context of creditor-debtor relationships. The study results show that the Court views parate executie as constitutionally valid, as long as it is carried out with the principles of transparency, proportionality, and the availability of legal recourse for the debtor. Therefore, legal protection within the mortgage system is not eliminated, but must be implemented through accountable and just practices. These findings provide an important normative basis for policymakers and economic actors in ensuring that the execution of guarantees runs effectively while still upholding the constitutional rights of the parties involved.